A Study on the Scenario of Shadow Banking System in India (International Journal of Innovative Research in Engineering & Management, 2021)
Whereas the origins of shadow bank might be the drawn back  to the 1970s, and the development of shadow banks in  underdeveloped nations has exploded in recent decades. The  recent bankruptcy of Infrastructures Leasing and Financial  Service (IL and FS) Limited Groups, a significant shadow  banks, interrupted the credit cycle, slowed investments, or even  impacted overall Gross domestic products (GDP) development  in India. Considering specialists warnings that the shadow bank  is vulnerable to systemics dangers and crises, it's more  important than ever to have a deeper understanding of the  system. The primary goal of this review study is to use  quantitative exploratory data analysis to emphasize the need for  efficiency in delivering information about shadow banks and  how they operate. Secondary sources of data are utilized to  study patterns in Indian shadow banking, uncover systemic  issues in the business, and propose regulatory solutions. A review is necessary to illustrate the significance of the shadow  banking’s sectors In India, its expansion, or the developing  regulatory involvements that regulate this critical  components of financial systems. For the foreseeable future,  shadow banking, in some form or another, is projected to  remain a major element of the financial system.
Keywords: Banking System; Financial Crisis; Mutual Funds